Intervention group logotherapy and performance measures for reducing phubbing in Generation Z - FATCHURAHMAN, Mohammad (2023)
ObjectiveThis study aims to explore in-depth how to apply logotherapy to people with phubbing.MethodsThe research methodology uses with mixed methods, a sequential approach used in this study for handling the phubbing population is 110 students. Samples taken by purposive sampling with attention to the range aged 10-25 years, and the research sample obtains as many as 16 students. The sample was determined based on the scale analysis results and recommendations from the school – research data from research instruments in observation sheets and qualitative data interviews. A Phubbing scale was used to get quantitative data.ResultsThe results of the study showed that there were better changes as evidenced by changes in phubbing scale scores before and after being given treatment.ConclusionThe study’s conclusion shows that Logotherapy Counseling effectively reduces phubbing in Generation Z.